Benson’s microbiological applications : - Benson, Harold J. (McGraw-Hill Higher Education, 2005)
The classic resource for undergraduate microbiology laboratory courses just keeps getting better. The self-contained, clearly illustrated exercises and four-color format make Microbiological Applications: A Laboratory Manual in General Microbiology the ideal lab manual. Appropriate for either a majors or non-majors lab course, Benson assumes no prior organic chemistry course has been taken